Implementasi Pembelajaran Pendidikan Pancasila Berbasis Tri Kaya Parisudha terhadap Pengembangan Karakter Siswa Sekolah Dasar - Kadek Andin Dwi Pratiwi; Kadek Rika Damayanti; Ni Luh Putu Nia Mylinda; I Ketut Ngurah Ardiawan (Journal on Education, 2024)
The teachings of Tri Kaya Parisudha are applied in Pancasila education in elementary schools with the aim of fostering constructive thoughts, speech, and behavior in order to develop good character in students. Using descriptive qualitative method, this research was conducted at SD Negeri 4 Tegalinggah. Information was collected through literature review, interviews and observations. The findings of this study demonstrate the effectiveness of Tri Kaya Parisudha in fostering character aligned with Pancasila. It consists of three components: Manacika (thinking good), Wacika (speaking good), and Kayika (doing good). This method has been shown to improve students' good attitude both inside and outside the classroom, which contributes to the achievement of the Pancasila learner profile